2013
DOI: 10.7567/jjap.52.08jg13
|View full text |Cite
|
Sign up to set email alerts
|

Green and Red Light-Emitting Diodes Based on Multilayer InGaN/GaN Dots Grown by Growth Interruption Method

Abstract: We have successfully implemented green and red light-emitting diodes (LEDs) based on InGaN/GaN quantum dots (QDs) grown by controlling the process of the growth interruption method using metal organic vapor phase epitaxy (MOVPE). It is found that the three-step growth interruption method and the underlying InGaN/GaN superlattice structure are beneficial for achieving greater indium incorporation in InGaN QDs. As a result, green and red LEDs with electroluminescence (EL) peak energies of 2.28 eV at 20 mA and 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Also, we have demonstrated 665-nm InGaN-based red LEDs on β-Ga 2 O 3 substrates, allowing very low forward voltages below 2.5 V at 20 mA [16]. Other groups have also reported several approaches to obtain high-In-content InGaN-based LEDs, including InGaN/GaN multiple quantum dots [17], semipolar InGaN buffer layers [18], InGaN/GaN nanowires [19], and InGaN/GaN QWs on lattice-matched InGaN/ScAlMgO 4 (0001) templates [20]. Additionally, a unique nitride-based red LED has also been reported, which utilizes Eu-doped GaN instead of InGaN as the active layer [21].…”
Section: Introductionmentioning
confidence: 86%
“…Also, we have demonstrated 665-nm InGaN-based red LEDs on β-Ga 2 O 3 substrates, allowing very low forward voltages below 2.5 V at 20 mA [16]. Other groups have also reported several approaches to obtain high-In-content InGaN-based LEDs, including InGaN/GaN multiple quantum dots [17], semipolar InGaN buffer layers [18], InGaN/GaN nanowires [19], and InGaN/GaN QWs on lattice-matched InGaN/ScAlMgO 4 (0001) templates [20]. Additionally, a unique nitride-based red LED has also been reported, which utilizes Eu-doped GaN instead of InGaN as the active layer [21].…”
Section: Introductionmentioning
confidence: 86%
“…Materials Synthesis and Device Fabrication : The InGaN QDs were grown on a 2 in. (0001) GaN/sapphire template in an AIXTRON 2000HT MOCVD system by using the growth interruption method . Graphene was prepared by a conventional chemical vapor deposition method using 25 µm Cu foil as the catalytic substrate and a mixture of CH 4 and H 2 as the precursor .…”
Section: Methodsmentioning
confidence: 99%
“…Oliver et al reported the realization of micro-disk InGaN laser on sapphire substrates via growth interruption method [21]. Other research groups also employ the similar growth interruption methods to improve the optical properties of light emitting devices [22][23][24][25]. In this work, we investigated the effect of different growth interruption time on the surface morphology and optical properties of InGaN QDs grown on 2-inch silicon substrates.…”
Section: Introductionmentioning
confidence: 99%